Pengembangan Instrumen Literasi Matematis Menggunakan Konteks Permainan Tradisional Banten untuk Siswa SMP - Wahyuningsih, Afrilia; Syamsuri, Syamsuri (Peneliti.net, 2025)
This research aims to develop and see the potential impact of mathematical literacy instruments in the context of traditional Banten games for junior high school students that are valid and realistic. This type of research uses a type of Research and Development (R&D) research with a Plomp development model which consists of five phase, namely the self-evaluation phase, expert review phase, one-to-one phase, small group phase, and field test phase. This research produced eight valid and realistic PISA mathematical literacy questions. The instrument has a potential impact seen from students' ability to: (1) apply a simple context using a mixed calculation operation to find percentage values; (2) using basic algorithms, formulas and procedures to solve problems; (3) follow the instructions that have been given in the form of pictures, tables and graphs clearly; (4) demonstrate a basic understanding of functional relationships as well as devise simple strategies to solve problems; (5) interpret sales data using graphs or tables that have been provided; (6) solve problems with undefined models obtained from reasoning skills; (7) formulating the average and communicating its arguments based on the results of the calculations obtained; and (8) have mastery of symbolic and formal mathematical operations and be able to explain the reasons for determining decision-making in relation to solutions and initial problems.